2016
DOI: 10.1088/1674-1056/25/9/090501
|View full text |Cite
|
Sign up to set email alerts
|

Current and efficiency optimization under oscillating forces in entropic barriers

Abstract: The transport of externally overdriven particles confined in entropic barriers is investigated under various types of oscillating and temporal forces. Temperature, load, and amplitude dependence of the particle current and energy conversion efficiency are investigated in three dimensions. For oscillating forces, the optimized temperature-load, amplitudetemperature, and amplitude-load intervals are determined when fixing the amplitude, load, and temperature, respectively. By using three-dimensional plots rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…(2019) 013211 nonequilibrium fluctuations. Those ratchets include forced thermal ratchets [4], rocking ratchets [5], flashing ratchets [6], correlation ratchets [7], entropic ratchets [8,9], and so on. This whole field presents an area of active research, as ratchet eects and the resulting net current can be utilized for applications like cargo transport, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) 013211 nonequilibrium fluctuations. Those ratchets include forced thermal ratchets [4], rocking ratchets [5], flashing ratchets [6], correlation ratchets [7], entropic ratchets [8,9], and so on. This whole field presents an area of active research, as ratchet eects and the resulting net current can be utilized for applications like cargo transport, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[5,11] It can be concluded that the correlated noises play a great role in the nonequilibrium motion process. In addition, there were also some studies on rocking ratchets, [12,13] the inertia ratchets, [14] feedback-control ratchet, [15] uncoupled neuron system, [16] the static bias, [17][18][19] mass separation, [20] entropy barrier, [21] the motion of fiber suspension, [22] nonmarkovian effect, [23] etc.…”
Section: Introductionmentioning
confidence: 99%